Epidemiology of Polymyxin Use in a Tertiary Care Setting of South India. (4th October 2017) - Menon, Vidya; Patel, Payal; Nampoothiri, Vrinda; Kumar, Anil; Mohamed, Zubair Umer; Sudhir, Sangita; Pogue, Jason; Singh, Sanjeev; Kaye, Keith S
Abstract: Background: Polymyxin B(PB) and Colistin (PE) use have increased in India due to emergence of resistant Gram-negative organisms. The Indian Council of Medical Research has identified carbapenems, polymyxins (PE and PB) as key antimicrobials which require restriction in hospitals. We describe epidemiology of PB and PE use following implementation of an Antibiotic Stewardship Program (ASP) in a 1300-bed, private, tertiary-care center in Southern India. Methods: An ASP was established at Amrita Hospital in Feb 2016 consisting of an administrative champion, hospitalist, microbiologist, intensivist and 5 pharmacists. Institutional guidelines for polymyxins were established and disseminated. The ASP team performed daily post-prescriptive reviews, evaluated and tracked appropriateness of PB and PE use, including administration of a loading dose (LD), maintenance dose (MD), frequency, route and duration of therapy. ASP recommendations and compliance were recorded. Results: During the 12-month study period (Feb '16-Jan '17), 348 patients received 295 PE and 94 PB courses. Mean age was 50 yrs and 73% were male. Patients on Medicine and Hematology/Oncology teams accounted for 42% of all prescriptions. The most common infections were bacteremia (34%), pneumonia (29%) and UTI (23%). Pathogens were recovered in 69% (269/389) of cases, Klebsiella pneumoniae 23% (90/389) and Acinetobacter baumanii 11 % (45/389) were most common. 290 (75%) of polymyxin course were judged to be inappropriate (78% of PE and 22% of PB). The most frequent reasons for inappropriate therapy included incorrect frequency of administration (64% for PB and 58% for PE), inappropriate MD (60% for PB and 48% for PE) and wrong duration of therapy (54% for PE and 48% for PB). 95% of incorrect MD for both PE and PB were too low. The reasons for inappropriateness were similar for both polymyxins.While all inappropriate LD episodes for PB ( n = 22 %) were due to lack of a LD, errors for PE ( n = 34%) involved either omission of LD or administration of LD that was too low.ASP recommendations were made in 190 instances with 58% provider compliance. Conclusion: Review of PB and PE use in our hospital indicates a high percentage of inappropriate use and highlights stewardship opportunities for improving care of patients with resistant infections. Disclosures: K. S. Kaye, Xellia: Consultant, Consulting fee; Merck: Consultant and Grant Investigator, Consulting fee and Research support; The Medicines Company: Consultant and Grant Investigator, Consulting fee and Research support